1996
DOI: 10.1016/s0035-9203(96)90120-0
|View full text |Cite
|
Sign up to set email alerts
|

Epileptic seizures and malaria in Kenyan children

Abstract: Between October 1990 and November 1991 data were collected on the frequency, causes, and nature of epileptic seizures in children admitted to the paediatric ward at Kilifi District Hospital, Kenya, from a defined study area. During this period, 1324 children were studied, of whom 15.8% had seizures as part of their illness. Malaria was by far the commonest cause of seizures, accounting for 69.0%; no other single condition caused more than 4.4%. The proportion of respiratory infections complicated by seizures w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
93
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(96 citation statements)
references
References 12 publications
2
93
0
1
Order By: Relevance
“…4,15 In a study of Nigerian infants who were Ͻ6 months, old, 41% of meningitis cases were reported to have a coexisting lower respiratory tract infection. 17 We therefore think that signs of lower respiratory tract infection should not bias clinicians against investigating and/or treating for meningitis when other indicators exist.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,15 In a study of Nigerian infants who were Ͻ6 months, old, 41% of meningitis cases were reported to have a coexisting lower respiratory tract infection. 17 We therefore think that signs of lower respiratory tract infection should not bias clinicians against investigating and/or treating for meningitis when other indicators exist.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, at our center, this age range also encompasses almost all of the admissions with malaria, the most common cause of seizures. 17 The optimum management of "seizures with fever" has been the subject of considerable debate in resource-rich countries for many years. Establishing the prevalence of meningitis in children with uncomplicated febrile convulsions, without signs of more serious disease, has been an essential step in defining current practice.…”
Section: Discussionmentioning
confidence: 99%
“…Seizures are a common feature of malarial disease, regardless of its severity. 25 They occur in up to 85% of admissions with a diagnosis of cerebral malaria, with about half of these having an episode of status epilepticus. 26 The probable origin of seizures associated with malaria fall into 3 basic categories: those that are febrile; those that are associated with the excitotoxic process related to the presence of parasites; and those that are related to hypoxia (Crawley J, unpublished data).…”
Section: Introductionmentioning
confidence: 99%
“…26 The probable origin of seizures associated with malaria fall into 3 basic categories: those that are febrile; those that are associated with the excitotoxic process related to the presence of parasites; and those that are related to hypoxia (Crawley J, unpublished data). 25,26 Uncomplicated febrile seizures will have a good prognosis. 27,28 However, as Ͼ 50% of seizures begin with low or normal temperatures, malaria appears to be specifically epileptogenic.…”
Section: Introductionmentioning
confidence: 99%
“…The proportion of complex acute seizures is higher than that in developed countries (60% vs. 30%) and may have a role in development of epilepsy 14, 15. We conducted a study to determine the risk of epilepsy after acute seizures and the associated factors in children admitted to a rural Kenyan hospital.…”
mentioning
confidence: 99%